Static and dynamic assessments of park accessibility and equity across different living circles in shenzhen’s core area - Zhongshan Huang; Qiyue Jia; Shixian Luo; Zhigang Tu; Lei Zhao; Siyuan Li; Zhengyan Lu (Environmental Research Communications)
With the rapid expansion of cities, the demand for park green spaces within urban living circles is increasing. Enhancing park accessibility and distributional equity has become an important avenue for improving urban residents’ quality of life. However, existing studies mainly rely on static population data, neglecting the impact of residents’ dynamic location changes on park accessibility, and lack a systematic analysis across different living circles. To fill this research gap, this paper takes the urban core area of Shenzhen as a case study. By combining static and dynamic population data and employing the improved dynamic two-step floating catchment area (D2SFCA) and the traditional two-step floating catchment area (2SFCA) methods, we systematically evaluate the walkability and equity of parks within different living circles (5-, 15-, and 30 min). The results show significant differences between static and dynamic population distributions, with overall park accessibility being lower for the dynamic population than for the static population. Within the 5 min living circle, the Gini coefficient for the static population is 0.952 but reaches as high as 0.971 for the dynamic population, indicating extreme inequity in park distribution within short walking distances. In the 15- and 30 min living circles, the Gini coefficients for the static population are 0.813 and 0.731, respectively, while those for the dynamic population are 0.882 and 0.785, indicating that the degree of inequitable park resource distribution decreases with increased walking time. Overall, the study reveals that park accessibility for the static population is significantly higher than that for the dynamic population across different living circles, especially within short-time living circles where the difference is most pronounced.